Using Web-Based Corpora to Find Norwegian Specialised Neologies - Kristiansen, Marita (Communication & Language at Work, 2012)
In this article I present an on-going study of the use of web-based corpora to detect Norwegian terminology and in particular financial neologisms. With an ever increasing influence from English in the domain, the use of anglicisms such as ‘dobbeldipp’ (‘double dip’) or ‘shortsalg’ (‘short selling’) is increasing rapidly. The study focuses on how to detect these specialised neologisms and also possible Norwegian terms that are formed. Three different corpora are used, i.e., the Norwegian Newspaper Corpus (NNC), Peter Warrens finansblogg (PW) and a blog on a research project which focuses on the financial crisis called Crisis, restructuring and Growth (KOV). The aim is to gather terminological information which can be useful in the NHH Termbase, an online, web-based termbase to be used by students, lecturers and researchers at the Norwegian School of Economics (NHH).